(untitled) - Golomb, Solomon W.; Soloman W. Golomb; Guang Gong (Cambridge,New York)
Wireless communications, advanced radar and sonar systems, and security systems for Internet transactions are contemporary examples of systems that employ digital signals to transmit information. This volume affords comprehensive, up-to-date treatment of the methodologies and application areas throughout the range of digital communication where individual signals, and sets of signals, with favorable correlation properties play a central role. Some application areas covered include Code Division Multiple Access (CDMA) signals such as those in use for cell-phone communication; digital systems for coded radar and sonar signals; and methods for secure authentication and stream cipher cryptology. The authors provide the necessary mathematical background to explain how the signals are generated and to show how the signals satisfy the appropriate correlation constraints
Includes bibliographical references and index
Keywords: Signal theory (Telecommunication); Signal processing